Rhesus pieces: genotype matching of RBCs - Hendrickson, Jeanne E. (Blood, 2018)
As Chou et al have elegantly shown in this issue of Blood,(1) RH genetic diversity in patients with sickle cell disease (SCD) is prevalent, and matching of donor and recipient red blood cell (RBC) antigens at the molecular level for transfusion is feasible. The Rh blood group system is highly complex, with many antigens defined at the serologic level encoded by the RHD and RHCE genes. Genetic exchange between RHD and RHCE is especially common in individuals of African descent, including those with SCD. In fact, ∼90% of studied patients with SCD have at least 1 RH allele that differs from those found in individuals of European descent.(2) Because most blood donors in the United States are not of African descent, each RBC transfusion thus exposes recipients with SCD to many “nonself” blood group antigens.